Induction and evaluation of acute inflammatory model of sulfur mustard analogue (CEES) in C57BL/6 mice - Tapak, Mahtab; Sadeghi, Somaye; Ghazanfari, Tooba; Mosaffa, Nariman (Student Research in Translational Medicine, 2023)
The acute threat model with mustard analogs has been produced and synthesized due to the dangers that sulfur mustard can pose to users in experimental work conditions and the creation of sulfur and numerous analogs to prevent its dangers. To evaluate the confirm of 2- Chloroethyl Ethyl Sulfide (CEES) as an analog of SM, we set up a new model of CEES systemic injection & exposure to be as close as possible role of this toxin analog effects on innate immune inflammation. Female C57BL/6 mice, 8-10- week old at the onset of the study, were exposed to CEES (10 mg / kg). The administration route was Intraperitoneal (IP) injection. At the end of the study, the mice’s lung fluid, and peritoneal lavage, spleen lymphocyte and lung tissue were extracted for future histopathological assessments.